A hybrid computer-brain interface via eye-tracking and EEG for disabled people - Ocampo, Myla Angelie Wingco (2016)
Technology advances through time and more applications have been developed and are available to accommodate to human needs not only in leisure but to support those with disabilities and illnesses through computer vision and human computer interaction technologies. Eye Tracking system and application is a good example of computer vision and human interaction technology. The application has been with us for a long period of time and it has made its mark in the field of medicine and computer science. In this project, it intends to utilize the capabilities of OpenCV with Microsoft visual studio to create a robust but least complicated Eye Tracking program which will be implemented on a system that will allow the user a medium of communication. The program will take into consideration the eye pupil’s location and its fixation which will allow to explore the gaze location. The eye detection has been successfully achieved by using Haar Classifiers. This report will cover the research and methodologies done behind the project. It will also cover the prototypes and the learning journey behind its development.